Dynamic and Static Quenching of Fluorescence by 1-4 nm Diameter Gold Monolayer-Protected Clusters - Cheng, P.; Silvester, Debbie; Wang, G.; Kalyuzhny, G.; Douglas, A.; Murray, R. (American Chemical Society, 2006)
How the efficiency of molecular quenching by Au nanoparticles depends on nanoparticle size is reported for (a) dynamic (collisional) quenching of four different fluorophores by three Au nanoparticles having similar protective layers but differing core diameters (1.1, 1.6, and 2.0 nm) and (b) static quenching in the electrostatic association between [Ru(bpy)3]2+ and five tiopronin-protected Au nanoparticles having core diameters from 1.3 to 3.9 nm. The quenching constants systematically increase with core size. In (a), the dynamic constants scale with the molar absorbance coefficients of the nanoparticles, showing the essentially of the absorbance/ emission spectral overlap, and the associated nanoparticle core density of electronic states, in energy-transfer quenching. In (b), the fluorescence of the Au nanoparticle itself was enhanced by energy transfer from the [Ru(bpy)3]2+ fluorophore.